Beta-Lactam/Beta-Lactamase Inhibitor Therapy for Potential AmpC-Producing Organisms: A Systematic Review and Meta-Analysis - Cheng, Matthew P (Open Forum Infect Dis, 2019)
The optimal treatment for potential AmpC-producing Enterobacteriaceae, including Serratia, Providencia, Citrobacter, Enterobacter, and Morganella species, remains unknown. An updated systematic review and meta-analysis of studies comparing beta-lactam/beta-lactamase inhibitors with carbapenems in the treatment of bloodstream infections with these pathogens found no significant difference in 30-day mortality (OR, 1.13; 95% CI, 0.58 – 2.20).